(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يعود تاريخ المسرح ذو الطابع الأوروبي الذي عرفته إيران إلى أواسط القرن التاسع عشر عندما عاد إلى إيران عدد من الخريجين الموفدين، الذين درسوا في أوروبا، والذين اطلعوا على الأدب المسرحي هناك وقاربوه مع ثقافتهم، وعملوا على ترجمة الكثير من المسرحيات الغربية إلى اللغة الفارسية؛ من مثل مسرحيات موليير وشكسبير إلخ . فقد بدأ المجتمع الإيراني يتعرف تدريجياً على الحضارة الغربية والسمات المميزة لها؛ إذ حصل انقلاب على صعيد المسرح الإيراني، وازدهر التأليف والترجمة المسرحية، وظهرت الفرق المسرحية القوية والمتميزة بأدائها، وشهدت هذه المرحلة تأسيس أول معهد مسرحي في إيران . لقد كانت المسرحيات التي قدمت من أثناء تلك السنوات تحمل في غالبيتها طابعاً سياسياً واجتماعياً وتاريخياً، وبعد انتصار الثورة الإسلامية في إيران ازداد الاهتمام بهذا الفن ولم يهمل النظام السياسي في الجمهورية الإسلامية المسرح. وبرز عدد لا يستهان به من كبار الكتاب والمفكرين على صعيد الأدب المسرحي والذين لعبوا دوراً مؤثراً في تطور هذا الفن الحديث بدءًا من آخوندزاده وصولاً إلى بهرام بيضايي وأكبر رادي إلخ . The history of European style-like drama in Iran dates back to the mid 19th C, the return of a number of Iranians who have studied in Europe and they were introduced to drama there. During that period, many western plays were translated into Persian, such as Moliere’s and Shakespeare’s… etc. The Iranian society, simultaneously with the constitutional revolution and the increase in political social and historical activities, gradually started to be acquainted with western civilization. Consequently, there was a revolution in Iranian drama: Translation and composition in drama flourished, and great theatrical groups came into being, in addition to the establishment of the first theatre training institute. The plays featured at that time were almost all political, social and historical. And after the victory of the Islamic Revolution in Iran, there was a greater concern in drama. Drama was not marginalized by the republican government, Great dramatists emerged, starting with Akhoundzada and not ending with Bahram Baizaei and Akbar Radi, and the like.